Winter Wheat Graze Out - Jones, Rodney; Sartwelle III, James D.; O'Brien, Daniel M. (My University, 1995)
This budget estimates short run costs and returns for both a steer and heifer wheat grazing program.
MF1010_1995-10
Keywords: MF1010; Economics; Livestock; Crops; MF